DEFECT FORMATION IN IRON-DOPED SILICON SINGLE CRYSTALS - Kh.S. Daliev; Z.M. Khusanov (Research Focus International Scientific Journal, 2023)
The effect of diffusion alloying with iron on the electrical properties of heat-treated silicon obtained by the Czochralski method has been studied. It is shown that the presence of iron reduces the concentration of nucleation centers for thermal donors of "growth" origin. The latter circumstance caused a decrease in their initial speed; on the other hand, the admixture of iron reduced the probability of decay of thermal donors, leading to their transformation into an electrically passive state, which led to an increase in the concentration of thermal donors during prolonged heating. Heat treatment at temperatures above 600°C caused the iron impurity to lose its electrical activity. Hardening of Si <Fe> crystals from 1100÷1200 °C for 10 hours returned the iron atoms to the electrically active substitution position.